Histatins in non-human primates: gene variations and functional effects. - Padovan, Lara; Segat, Ludovica; Pontillo, Alessandra; Antcheva, Nikolinka; Tossi, Alessandro; Crovella, Sergio (Protein Pept Lett, 2010)
Human histatins are histidine-rich, low molecular weight salivary proteins that contribute to the immune system of the oral cavity. In this work, nucleotide sequences of the HIS1 (coding for histatin 1) and HIS2 (coding for histatin 3) genes, homologous to the human ones, have been sequenced and analysed in five primates species including Great Ape, Hylobatidae and Cercopithecidae. In HIS1, the region corresponding to the putative mature peptide shows a premature stop codon in Macaca and Cercopithecus, while HIS2 a six codon insertion in the Cercopithecidae. Histatin 5, a 24-residue peptide derived from histatin 3, is the most antimicrobially active among human histatins, thus macaque and nomascus orthologues of histatin 5 were selected for chemical synthesis and functional characterization, in comparison to the human peptide. All synthesized histatins are predicted to be poorly amphipathic, depending on the charged state of His residues and assume partially a-helical conformations only in lipophilic conditions. Antimicrobial assays against Candida and Criptococcus spp. indicate somewhat different spectra of in vitro activity against the tested fungi. We have described HIS1 and HIS2 gene variations in primates and have analysed their functional effects on selected Hst5 orthologues. The human antimicrobial peptide has been proposed to represent an important lead for new generation of antimicrobial compounds for the treatment of oral mycoses, thus the information from the non-human primates histatins studied may aid strategies for drugs design.
Keywords: Amino Acid Sequence; Animals; Anti-Infective Agents; Base Sequence; Candida; Catarrhini; Cell Proliferation; Computational Biology; Cryptococcus; Genetic Variation; Histatins; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA